Challenges of Covid-19 towards Malaysian Employment / Mohamad Aqil Abd Hamid, Nurul Hidayana Mohd Noor and Aida Abdullah - Abd Hamid, Mohamad Aqil; Mohd Noor, Nurul Hidayana; Abdullah, Aida (2021)
Covid-19 was declared a global pandemic by the World Health Organization (WHO) on March 11, 2020, the first time since H1N1 influenza was declared a pandemic in 2009 (World Health Organization, 2020). Further, it is a global pandemic and public health emergency that has had a significant impact on the global economy and financial markets whereby the disease mitigation measures that have been implemented in many countries have resulted in significant income reductions, increased unemployment, and disruptions in the transportation, service, and manufacturing industries (Anton Pak, 2020). The pandemic of Covid-19 has impacted negatively on labor markets, with disproportionately negative consequences for employment. Demand has sunk as a result of lockdowns and travel restrictions, forcing many businesses to close or scale back operations, putting workers at risk (Asian Development Bank & International Labour Organization, 2020). From this point, this pandemic Covid-19 influences employment. In Malaysia, a recent study found that more than half of work is particularly vulnerable to Covid-19 (Amanina Rahman, 2020). There are still few studies conducted in addressing the challenges faced by employment during this pandemic. But one remains clear which is the issue that has been faced by society when dealing with employment during this pandemic effect are undeniable. In this paper, the researchers explain the effect of Covid-19 that poses challenges towards Malaysian employment.